Differentiated Instruction: Analysis of Elementary School Teachers’ Understanding in Bali Q-Ta School: Pembelajaran Berdiferensiasi: Analisis Pemahaman Guru Sekolah Dasar di Sekolah Bali Q-Ta - Witraguna, Kadek Yudista; Jaya, I Ketut Manik Asta (Pedagogia : Jurnal Pendidikan, 2024)
Differentiated instruction is implemented to support the application of the Merdeka Curriculum. Teachers need to have a good understanding before implementing differentiated instruction. The study aims to determine and analyze the understanding of elementary school teachers regarding differentiated instruction at Bali Q-Ta School (SD Bali Q-Ta), as well as to identify the constraints in its implementation. The research was conducted using mixed methods. The subjects of this study were all elementary school teachers at SD Bali Q-Ta. Research data was obtained using questionnaires and interviews. The data obtained were analyzed descriptively. Findings indicate that the understanding of elementary school teachers at SD Bali Q-Ta falls into the "very good" category, with an average score of 77.9. The constraints faced by elementary school teachers at SD Bali Q-Ta include: (1) the preparation, implementation, and evaluation requiring a significant amount of time; (2) difficulties in preparing diverse teaching aids; (3) errors in diagnosing student needs; and (4) difficulties in developing suitable assessment instruments tailored to student needs Highlights: Differentiated Instruction: Tailoring teaching methods to accommodate diverse student needs. Merdeka Curriculum: Framework for Indonesian education emphasizing autonomy and innovation. Elementary School Teachers: Key agents in implementing differentiated instruction effectively. Keywords: Differentiated Intruction, Merdeka Curriculum, Teachers Understanding